Effect of Magnetic Field on the Corrosion Characteristics of AZ31B Magnesium Alloy in NaCl Solutions with Two Different Concentrations - JIANG Chao, MA Bao-ji (Cailiao Baohu, 2021)
For studying the effect of magnetic field on the corrosion behavior of AZ31B magnesium alloy in NaCl solutions with two different concentrations, the magnetic field intensity distribution of the magnetic field in the electrochemical reaction system was analyzed by COMSOL, and the dynamic potential polarization and electrochemical impedance of AZ31B magnesium alloy in 0.1 mol/L and 1.0 mol/L NaCl solution were studied under magnetic field.Results showed that after adding 400 mT magnetic field by simulation, the magnetic field intensity distribution on the magnesium alloy surface became uneven.In 0.1 mol/L NaCl solution, the self-corrosion potential of AZ31B magnesium alloy increased, the corrosion current decreased and the pitting amount decreased, signaling that the corrosion rate of magnesium alloy decreased after adding 400 mT magnetic field.In 1.0 mol/L NaCl solution, after adding 400 mT magnetic field, the self-corrosion potential of AZ31B magnesium alloy shifted negatively, the corrosion current increased, the number of pitting corrosions increased then the pitting connected with each other and the passivation film broke, which indicated the corrosion rate of AZ31B magnesium alloy in high concentration NaCl solution increased.